2023
DOI: 10.1213/ane.0000000000006364
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Radiological Assessments of Injectate Spread Stratified by the Volume of the Pericapsular Nerve Group Block

Abstract: BACKGROUND:The pericapsular nerve group (PENG) block was recently suggested as a regional technique for managing acute pain after hip surgery. However, few anatomical studies have confirmed the spread of injectate during the PENG block. This cadaver study aimed to analyze injectate spread to the target nerves during single-injection ultrasound-guided PENG block. METHODS: Ultrasound-guided PENG block with 3 different injectate volumes (10, 20, or 30 mL) was performed in 18 cadavers. Injectate spread by the volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…And a recent cadaveric study 16 indicated that for PENG block, the maximum effective volume of dye in 90% of cases (MEV90) of methylene blue required to spare the FN is 13.2 mL, which indicates that motor weakness may result from high volume of ropivacaine spread to FN. Furthermore, Kim JY 23 reported the anatomical spread of injectate during PENG block and found that the articular branches of the FN were stained with dye in nearly all 20 mL and 30 mL specimens, which was consistent with the quadriceps weakness observed clinically after PENG block. In addition, theoretically, if PENG block only blocks the sensory fibres, the change in concentration will not lead to a change in postoperative muscle strength but will only affect the postoperative sensation at most.…”
Section: Discussionsupporting
confidence: 58%
“…And a recent cadaveric study 16 indicated that for PENG block, the maximum effective volume of dye in 90% of cases (MEV90) of methylene blue required to spare the FN is 13.2 mL, which indicates that motor weakness may result from high volume of ropivacaine spread to FN. Furthermore, Kim JY 23 reported the anatomical spread of injectate during PENG block and found that the articular branches of the FN were stained with dye in nearly all 20 mL and 30 mL specimens, which was consistent with the quadriceps weakness observed clinically after PENG block. In addition, theoretically, if PENG block only blocks the sensory fibres, the change in concentration will not lead to a change in postoperative muscle strength but will only affect the postoperative sensation at most.…”
Section: Discussionsupporting
confidence: 58%
“…For example, Ahiskalioglu et al determined that injecting a 30 ml volume of local anesthetic when performing a PENG block can result in the upward diffusion of the anesthetic, potentially resulting in a lumbar plexus block-like effect [ 15 ]. In a recent anatomical study, simultaneous staining of the femoral nerve was observed in 6/12 (50%) 20 ml specimens and 12/12 (100%) 30 ml specimens [ 16 ]. Additional randomized controlled clinical studies will be necessary to clarify whether high-volume PENG block can replace lumbar plexus block.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the LA volume used in our study, the 20 mL administered for the PENG block reflects the volume recommended by Girón-Arango et al [ 11 ]. A high-volume PENG block might not be an ideal option, and persistent postoperative pain may be partially attributed to the lack of an obturator nerve articular branch blockade [ 24 ]. In a 2015 LPB dose-finding trial, Sauter et al [ 25 ] concluded that the minimum effective volume of 0.5% ropivacaine in 95% of patients (ED95) was 36 mL.…”
Section: Discussionmentioning
confidence: 99%
“…The superior performance of the PENG block may be due to the patient’s posture during the procedure (a supine versus a lateral decubitus). The time to analgesic requirement indicates that the PENG block may result in shorter analgesia and reduced total intravenous fentanyl consumption over 24 h. We speculate that the reduced block duration is a result of the injected LA spreading around the pericapsule, causing a dispersion effect [ 24 ], and that the concentration of the LA in one large muscle affects the duration of the pain block [ 17 ]. Our results were limited to single-injection blocks and further studies are needed to confirm our findings regarding continuous PENG blocks and LPBs.…”
Section: Discussionmentioning
confidence: 99%